Operational Delays in Automotive Service Contracts: A Fiqh Muamalah and Islamic Economic Law Analysis of an Ijarah Case - Adriansah Simatupang; Annio Indah Lestari Nasution; Atikah (Al-Amwal : Journal of Islamic Economic Law, 2025)
Purpose  – This study aims to examine the factors contributing to operational delays at Pak Tupang’s Car Repair Workshop in Airapa Village and to analyze their legal and ethical implications from the perspectives of fiqh muamalah and Islamic economic law. Specifically, the research focuses on evaluating the conformity of workshop practices with the principles of ijarah, Islamic work ethics, and maqāṣid al-sharī‘ah within the context of service-based contracts. Method – This research employs a qualitative approach with a normative–empirical case study design. Data were collected through direct observation, in-depth interviews with the workshop owner, employees, and customers, and documentation analysis. The collected data were analyzed thematically and interpreted using fiqh muamalah principles, Islamic work ethics, and maqāṣid al-sharī‘ah as the analytical framework.   Result and Discussion – The findings indicate that operational delays at Pak Tupang’s workshop are primarily caused by a shortage of skilled labor, manual and unstructured operational management, and limited availability of spare parts. These conditions result in uncertainty regarding service completion time and frequent deviations from initial repair estimates. From the perspective of fiqh muamalah, such practices may lead to gharar and darar within ijarah contracts, as the element of time certainty is not adequately fulfilled. The absence of standard operating procedures (SOPs) and structured supervision further reflects weak internal business governance and suboptimal implementation of Islamic work ethics, particularly the principles of amanah and itqān. Implication – This study highlights the necessity of strengthening internal business governance through the implementation of (SOP)’s grounded in Islamic business ethics, improving workforce professionalism, and enhancing operational supervision. These measures are essential to ensure contractual certainty, protect consumer rights, and align workshop practices with the objectives of maqāṣid al-sharī‘ah and consumer protection principles under Islamic economic law.